False-positive blood culture results in patients with hematologic malignancies. Issue 5 (May 2019) - Ebihara, Yasuhiro; Kobayashi, Kiyoko; Watanabe, Noriyuki; Taji, Yoshitada; Maeda, Tomoya; Takahashi, Naoki; Ishida, Akaru; Asou, Norio; Ikebuchi, Kenji
Abstract: Blood cultures are the most valuable tool when bacteremia is clinically suspected. Technical advances have led to the development of automated blood culture systems to detect bacterial infections. Usually positive signals in automated blood culture systems result from the proliferation of microorganisms. Cases are classified as false-positive when the automated blood culture system produces a positive signal but no microorganisms are detected on Gram-stained smears and no microorganism growth is observed in blood subcultures. False-positive blood culture results are very rare in patients with hematologic malignancies. Recently, we encountered four patients who had false-positive blood culture results. Two of the patients were diagnosed with acute leukemia, involving hyperleukocytosis and an excess of blasts. The other two patients were diagnosed with acute leukemia and diffuse large B cell lymphoma with leukocytopenia. Although hypercapnia or acidosis, apart from hyperleukocytosis, might also cause false-positive results, our cases clearly did not have these conditions. We should be aware of the possibility that false-positive blood culture results can occur in patients with leukocytopenia, as well as hyperleukocytosis. To understand the mechanisms responsible for the observed false-positive results, additional studies are needed after the accumulation of similar cases.